If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 6 = 9999999999999999999999999999999999999999999999999999999999888888888888888887 Reorder the terms: 6 + 11x = 9999999999999999999999999999999999999999999999999999999999888888888888888887 Solving 6 + 11x = 9999999999999999999999999999999999999999999999999999999999888888888888888887 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 11x = 9999999999999999999999999999999999999999999999999999999999888888888888888887 + -6 Combine like terms: 6 + -6 = 0 0 + 11x = 9999999999999999999999999999999999999999999999999999999999888888888888888887 + -6 11x = 9999999999999999999999999999999999999999999999999999999999888888888888888887 + -6 Combine like terms: 9999999999999999999999999999999999999999999999999999999999888888888888888887 + -6 = 9999999999999999999999999999999999999999999999999999999999888888888888888881 11x = 9999999999999999999999999999999999999999999999999999999999888888888888888881 Divide each side by '11'. x = 909090909100000000000000000000000000000000000000000000000000000000000000000 Simplifying x = 909090909100000000000000000000000000000000000000000000000000000000000000000
| .5(2x-6)-2(3x+1)=10 | | 5z-7=7z-3z | | -8-9=3x+5+2x | | 1/2(5x+9)=7x | | 10=6x-7 | | 7-5z=32 | | -8(2t-(4-7))= | | (3y+2)dx-(5x-7)dy=0 | | 15x+-10=-9x+2 | | -9x-9y=0 | | 1=0.4x-0.6x-17 | | 4x+3x-6-6=10+3 | | 3x^2=3-4x | | -3n+5n=38 | | x=2500-5x | | 3.5-h=42 | | w=y(r+A) | | 3.5+42=h | | 14k-5=65 | | z+9=126 | | 183/5+29/28-11/28 | | 5+105(2d-1)=.5 | | 6s-14=-6s+5 | | 8+11t-5=6t+66-4t | | 3.5+h=42 | | -8x-x+5=-6+5-3x | | T^3+12t^2-2t-24=0 | | 3x-121 | | Y-12=3x | | 4+-2p=6 | | 3/2x-6x=1/4x+4 | | 7z+9z=128 |